Características anatômicas e fisiológicas de Coffea arabica em condições de cerrado - Santos, Cyntia Stephânia dos (2017)
Leaf anatomy and physiology may help identify the cultivars that are more adapted to certain environmental conditions. This work aimed at characterizing genotypes of Coffea arabica in Cerrado of the Brazilian Highlands, by analyzing their anatomy and physiology. We analyzed genotypes of coffee plants from the Germplasm Bank of the Brazilian Agricultural Research Corporation (EMBRAPA Cerrados) located in the city of Planaltina, Distrito Federal. We used a fully randomized design, with 23 genotypes and 6 repetitions. The genotypes we analyzed were: Acaiá Cerrado MG1474, Araponga MG1, Catiguá MG1, Catiguá MG2, Catiguá MG3, Catiguá MG3 P4, Catiguá MG3 P5, Catiguá MG3 P7, Catiguá MG3 P9, Catiguá MG3 P23, Catiguá MG3 P51, Catuaí Amarelo IAC 62, Catuaí Vermelho IAC 15, Catuaí Vermelho IAC 81, Catuaí Vermelho IAC 99, Caturra Vermelho MG0187, Guatenano Colis MG0207, Mundo Novo IAC 379-19, Paraíso MG1, Pau Brasil MG1, Sacramento MG1, San Ramon MG0198 and Topázio MG-1190. We evaluated the thickness of the adaxial cuticle, the adaxial and abaxial epidermis, the spongy parenchyma and the palisade parenchyma, the mesophyll, the phloem, the number and diameter of xylem vessels; stoma density and functionality; leaf area index, amount of chlorophyll, and gas exchanges. We used multivariate analyses to differentiate the genotypes and the relevant variables. There was a difference in the behavior of the genotypes we evaluated, because some of them had characteristics that were more adapted to the cultivation conditions. The grouping analyses based on methods Tocher and UPGM separated the genotypes into ten groups, and genotypes Catiguá MG1, Catiguá MG2 and Mundo Novo IAC 379-19 remained in isolated groups, since they were the most divergent ones. The analysis of relative contribution of characteristics showed the amount of total chlorophyll, chlorophyll b, thickness of the spongy parenchyma, thickness of the mesophyll, and amount of chlorophyll a, as the variables that contributed the most with the divergence among the genotypes. Therefore, the genotypes of Coffea arabica we evaluated had differences regarding anatomical and physiological characteristics, showing that they adapted to the climatic conditions of Cerrado in the Brazilian Highlands. The most divergent genotypes were Mundo Novo IAC 379-19, Catiguá MG2 and Catiguá MG1; thus, they are the most suitable cultivars for future hybridizations in coffee plant breeding programs.